2016
DOI: 10.1097/rli.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Assessment of Nonionic Iodinated Radiographic Molecules as Chemical Exchange Saturation Transfer Magnetic Resonance Imaging Tumor Perfusion Agents

Abstract: The obtained results demonstrate that iohexol and ioversol, 2 commonly used radiographic compounds, can be used as MRI perfusion agents, particularly useful when serial images acquisitions are needed to complement CT information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…Although this simple estimate does not provide information on glomerular filtration rate or on renal blood flow, it was found to be correlated with the severity and with the evolution of the kidney damage. In addition, proof‐of‐concept studies have demonstrated that iopamidol and other radiographic agents can also provide perfusion estimates …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this simple estimate does not provide information on glomerular filtration rate or on renal blood flow, it was found to be correlated with the severity and with the evolution of the kidney damage. In addition, proof‐of‐concept studies have demonstrated that iopamidol and other radiographic agents can also provide perfusion estimates …”
Section: Discussionmentioning
confidence: 99%
“…37,38 In this study, renal pH values of the injured kidney significantly increased after AKI relative to the contralateral one, at both the ische- iopamidol and other radiographic agents can also provide perfusion estimates. 44,45 Nevertheless, a major limitation of all these approaches relies in the assessment of only one function of the kidneys, that is, their filtration capability, while the balance of the acid-base homeostasis has never been addressed. It is important to recognize that disordered acid-base homeostasis contributes to the progression of chronic kidney disease and to increased morbidity and mortality in dialyzed patients.…”
Section: Cest Renal Filtration Fraction Distinguishes Between Kidnementioning
confidence: 99%
“…Therefore, DR 1r and S r can provide images that are sensitive specifically to iohexol concentration and pH, respectively. The red line in Figure 3e is the best fit of Equation [4], which is used for pH calibration in the animal studies. k b , pH w , and Dv s in Equation [4] are fitted to be 0.98, 3.45 and 2977 s À1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The rat jugular vein was catheterized for intravenous injection. A 2‐mL 1.3‐M iohexol solution (in saline), according to a previous publication , was injected into each rat in 1 to 2 min. This corresponds for a 250‐g rat to a dose of approximately 4g I/kg body weight.…”
Section: Methodsmentioning
confidence: 99%
“…According to these considerations, researchers firstly turned their attention to already clinically approved contrast agents, such as iodinated contrast media, exploiting their high safety profile and FDA approval (Aime et al, 2005b;Longo et al, 2011). Consequently, radiographic agents have been exploited for assessing tumor microenvironment properties, including perfusion (Anemone et al, 2017;Longo et al, 2016b), acidosis (Chen et al, 2015;Jones et al, 2015;Longo et al, 2016a;Longo et al, 2014b;Sun et al, 2014) and for assessing renal functionality (Longo et al, 2013;Longo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%